Cape Town - Africa' Gateway. A traveller' and cultural guide to Cape Town and surrounds, with educational Xhosa language phrases" : development and evaluation of a hypermedia application for language learning - Janse van Rensburg, Charise (Stellenbosch : Stellenbosch University, 2012)
Thesis (MPhil)--University of Stellenbosch, 2004.